Papua New Guinea - Anti-Money Laundering and Combating the Financing of Terrorism : Mutual Evaluation Report - World Bank (Washington, DC, 2013)
Papua New Guinea (PNG) faces very serious risks of Money laundering (ML) from various criminal activities including domestic corruption (misappropriation of public funds), which is considered a serious problem. PNG is experiencing rapid economic growth, very large scale foreign investment and an escalating crime rate. While the Financial Intelligence Unit (FIU) is building its capacity, there is no clear political level commitment to 'follow the money' to tackle corruption and other crimes, and no demonstrated commitment to regulate and supervise AML obligations by financial sector regulators, which severely hampers the authorities ability to tackle financial aspects of corruption. Misappropriation of government funds occurs using government payments which, according to the authorities, are generally placed through the banking sector in PNG and used to purchase real estate, high-value vehicles, distributed in cash or moved offshore. This report provides a summary of the Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) measures in place in PNG at the time of the mission or shortly thereafter. The report was produced by the World Bank as part of the Financial Sector Assessment Program (FSAP) of PNG.